SENTIMENT ANALYSIS OF HACKER INTERNET FORUMS - Mambetov С.Т.; Begimbayeva Е.Е.; Khikmetov А.К.; Joldasbayev С.К.; Kazbekova Г.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
This article presents an overview and study of sentiment analysis techniques in the context of hacking internet forums. Hacker forums are a forum for exchanging information and experiences about computer security, and analyzing the emotional color of messages in such forums can provide useful insights into the study of hacker communities and their activities. Various methods and approaches are considered in the article. Methods considered include sentiment dictionary, machine learning, sentiment analysis, as well as hybrid models that combine these approaches. The principles and methodologies of each method, as well as their advantages and limitations, are described in detail. In addition, the article discusses the results and conclusions obtained when applying sentiment analysis to hacking forums. The results of the research allow us to better understand the emotional component in the hacker community, identify trends and moods, and identify potentially dangerous activities or trends. At the end of the article, general conclusions are drawn and possible directions of further research in the field of analysis of hacker Internet forums are indicated. Recommendations for using the analysis results to increase security and combat cybercrime are also provided.